Evolução geoambiental e geohistórica das dunas costeiras do município de Fortaleza, CE - Pinheiro, Mônica Virna de Aguiar (2009)
The coastal zone of Fortaleza City, object of our study, has an extensive coastal area, with different natural environments, now situated in a urbanized context. Among those environments, dunes have a special place. Large dunefields occurred in Fortaleza in prior times, but most are destroyed, only resisting in punctual segments of the city. In this research, we analyze the dunes of a natural point of view, as well as the process of their destruction. In the first perspective, we present a geoenvironmental evolution of the local dunes systems. In the second perspective, we analyze the urban development and the situation of dunes, in view of a subsequent contribution for better forms of use and adequate management of these natural elements. By this way, we present an analysis of Fortaleza City under historical and natural aspects, guided by the (1) environmental analysis, which integrates social and natural aspects in the understanding of the landscape and by (2) an geohistorical approach, innovative, where we made a review on the social process of occupation of the space, giving emphasis to the alterations in the natural environment. Associated with those methodological approaches, we used an assembly of necessary techniques to the achievement of the present work. From then, we analyze the main morphologies of dunes in the study area, as well as its classification in regards to their origin and age, by the meaning of dating, with thermal methods, two dunefields of the urban area of Fortaleza, the first dating to be carried out in the city, in order to deepen the knowledge about the natural evolution of the local dunefields. The dated dunes are situated at important points of the city, in the neighborhoods of Cocó and Sabiaguaba, with ages varying between 1,7ka and 2.2 ka, inserted in a generation of specific forms. In Fortaleza, since the period of the Portuguese colonization, dunes were being replaced by urban forms and artificial structures. We quantified the area of disappearing of dunes, since the decade of 1950 until 2008, which showed an irreversible and worrying chart for the matter. The geomorphological mapping was made by dividing the city in three segments (Beach of the Future, Sabiaguaba and sector West), as well as in regard to the quantification of dunes destruction. The final data results as an important tool of spatial analysis of environment and of the society x nature relationship. Nowadays, only few residual fields of dunes still remain in the city, and under eminent risk of complete degradation. In that sense, it seems urgent the definition of a better management and planning of the city, to conjugate urban growth with environment preservation.